Subtotal Calcanectomy for the Treatment of Chronic Ulcer Associated with Osteomyelitis: A Case Report - Faleiro, Thiago Batista (J Orthop Case Rep, 2017)
INTRODUCTION: Subtotal calcanectomy is a therapeutic option for the treatment of chronic ulcer associated with calcaneal osteomyelitis. Closure of the surgical wound can be difficult due to the lack of local cutaneous coverage. We present the first case of subtotal calcanectomy in which the ankle was positioned in plantar flexion allowing the primary closure of the surgical wound without the need for flap. CASE REPORT: We present a case of 62-year-old female patient with a foot ulcer associated with osteomyelitis. After an initial assessment, a subtotal calcanectomy with primary wound closure was performed. After healing of the surgical wound, the patient started rehabilitation with recovery of dorsiflexion and independent gait without support after 12 weeks. CONCLUSION: The result shows that subtotal calcanectomy with the ankle in plantar flexion allows primary closure of the operative wound, without causing difficulty for rehabilitation.